Sistem Perencanaan Manajemen Logistik Obat di Puskesmas - Eviyan, Putri; Indrawati, Fitri (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Drug planning is a process of selecting drugs and health supplies to determine the type and amount of drugs in order to meet drug needs at the puskesmas. Planning for drug needs at the Waruroyom Health Center is still not in accordance with real needs. This is often a gap between the drug requirements requested by the puskesmas and the drugs provided by the health office. The purpose of this study was to find out about the drug planning process at the Waruroyom Public Health Center Methods: this type of research is a qualitative research with in-depth interview method, the data is collected by means of observation, documentation, and the validity of the data using triangulation techniques. Results: The results showed that the drug planning process still had obstacles in the process of calculating drug requirements so that it still caused vacancies and excess quantities of drugs that could affect the process of procuring drug needs and losses due to the accumulation of drug stock. Conclusion: Based on the research results of the Waruroyom Health Center to increase knowledge of calculating drug needs for drug needs planning managers to apply the EOQ, ROP, and Safety stock calculation methods to avoid drug vacancies and excess drug stock and combine ABC and VEN methods in determining the types of drugs that will be prioritized to be administered.